Valproic acid thermally destabilizes and inhibits SpyCas9 activity - Cheng, Xinlai (Molecular therapy, 2020)
The clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 system plays an important role in prokaryotic adaptive immunity. Due to its capacity for sequence-specific gene editing, CRISPR-Cas9 has become one of the most important tools widely used for genome editing in molecular biotechnology. However, its clinical application is currently limited by unwanted mutations at off-target sites. Various strategies have been developed for precise control of Cas9 in order to reduce these off-target effects, including chemical-based approaches. From a chemical screening, I observed that valproic acid (VPA) binds to and destabilizes Streptococcus pyogenes Cas9 (SpyCas9) protein in vitro, as well as in cells, while within its therapeutical concentration range under conditions of hyperthermia as demonstrated. Conditions were generated either by an external heat bag or in combination with the photothermal therapeutic agent indocyanine green activated by a near-infrared laser. Use of other histone deacetylase inhibitors failed, suggesting a histone deacetylase inhibition-independent function of VPA. Thus, this finding provides an uncomplicated thermotherapeutical approach for timely regulation of the activity of the CRISPR-Cas9 system at desired locations.
Gesehen am 16.02.2022